Água subterrânea e a saúde da comunidade em bairro de Santa Maria - RS - Kemerich, Pedro Daniel da Cunha (2008)
The objective of the present work was to make a cadaster of water supply alternative sources in Nossa Senhora do Perpétuo Socorro neighborhood, assess the water physical-chemical and bacteriological quality of these sources, generate theme maps emphasizing the vulnerability to the underground water contamination, identify the occurrence of diseases from the hydric transmission in the community, and provide subsidies for the aware use and management of the underground resources. The alternative source users cadaster was carried out through visits to their residences, noting the well number and types, location in UTM coordinates, static levels, and their building and maintenance situations. It was still applied questionaries in each residence in order to obtain social-environmental data regarding the users of these alternative sources. Samples from the tubular wells, excavated wells and nascents found functioning were collected for determining the water quality. The GOD methodology was utilized for defining the vulnerability indices of the different areas represented by geo-morphological units. To identify hydric transmission diseases, the neighborhood residents blood and feces collect and analysis was done. At last, a first book about the necessary cares with the underground water was delivered. Several wells which presented non accordance of construction and/or according to the NBR 12224/2006 were observed. These are worrying factors that can generate the underground water contamination. Among the analyzed wells, those excavated were the ones that more surpassed the maximum value permitted for the parameter color. In total 13.63% were over the established as maximum in the Governmental Directive n°. 518/2004. In the muddiness parameter 18.18% of the samples are over the VMP recommended in the Directive 518/2004. The pH of the water samples had a wide variation between 4.24 to 8.2, while the variation range established by Directive 518 of the Ministry of Health is from 6.0 to 9.5. With respect to water hardness, the variation of its concentration happened from 4.96 to 800.57mg/L of CaCO3, being that the Directive 518/2004, ranks as drinking water those that present values inferior to 500mg/L of CaCO3. The sodium concentration values in the water samples varied from 2 to 112mg/L, being under the maximum limit established by the Directive 518/2004 which is 200mg/L. In relation to the results obtained in the Total Coliform determination, 43.18% of the alternative sources showed contamination and 40.90% presented fecal coliform contamination. In the excavated wells, it was evidenced a natural vulnerability to the contamination varying from medium to high. Though, in the sources the vulnerability was worthless. Through the blood sample analysis results collected from the supplying alternative source users, one obtains 0% of positiveness in relation to the Hepatitis A and in relation to the feces sample analysis. None presented cysts, eggs and larvae of parasites. Because of the results, it was concluded that the constant water quality monitoring in the alternative source user communities is important, this way avoiding problems related to the human health.